2004
DOI: 10.1017/s1047951104001234
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the practice of fetal cardiology in Europe

Abstract: F ETAL CARDIOLOGY IS CURRENTLY PRACTISED IN most European countries, but even within countries there is a great variation in the service provided. The recommendations provided in this document are intended to be guide for all paediatric cardiologists undertaking fetal echocardiography with the view of providing a service in fetal cardiology. It is clear that the health and legal systems vary from country to country, so that not all aspects of these recommendations can be implemented in all countries. The recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 0 publications
2
55
0
2
Order By: Relevance
“…The high-risk group comprised pregnant women referred for reasons known to be indications for FE (5). Low-risk group included pregnant women referred by an obstetrician for reasons other than indications of FE (5) or presented on their own will for screening with no obvious high-risk.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The high-risk group comprised pregnant women referred for reasons known to be indications for FE (5). Low-risk group included pregnant women referred by an obstetrician for reasons other than indications of FE (5) or presented on their own will for screening with no obvious high-risk.…”
Section: Study Populationmentioning
confidence: 99%
“…Complex heart defects or chromosome anomalies associated with heart defects may result in early fetal loss or still birth. Today, FE is recommended to all patients with high-risk pregnancies for fetal CHD (5). The frequency of CHD in low-risk pregnancies and in the screening groups were found to be higher than the live birth rate (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…August 11,2015 methods to evaluate and maintain quality and to establish performance standards. 2 There has also been a recent initiative to develop tools for assessment of quality and accuracy in performing and reporting pediatric echocardiograms.…”
Section: E58 Circulationmentioning
confidence: 99%
“…[8][9][10][11] As with TEE, some trainees may wish to attain a higher level of competency in performing and interpreting fetal echocardiography during core fellowship.…”
Section: Fetal Echocardiographymentioning
confidence: 99%
“…The information that is available suggests that, regardless of surgical approach, staged surgical reconstruction or transplantation, long-term functional and cognitive behavior is strongly related to initial condition at diagnosis, and hence is variable [29][30][31]. Prenatal diagnosis, fetal intervention, and its impact on survival after the first stage of palliation, are areas of current study [32][33][34]. The limited information available has suggested that infants diagnosed during the prenatal period are more likely to survive the initial stage of palliation as compared to those that are not diagnosed during the prenatal period [35].…”
Section: Unresolved Questionsmentioning
confidence: 99%